Essays in stock market anomalies - Yu, Lin (2016)
This thesis compromises one literature review chapter and three essays which focus on the theme of valuation, value premium anomaly, R&D premium anomaly, momentum anomaly and emerging markets. The first essay is entitled “Does Low Book-to-market Predict Low Returns? The Other Side of Growth: Research and Development Investment”. In this essay, I develop a theoretical framework of the risk and return of R&D, and examine the relation between R&D and BM. This paper documents that the intersections of R&D and BM produce enhanced trading strategies, and that the four-factor model, with a R&D factor, outperforms the three-factor model. The second essay, entitled “Firm Characteristics and Momentum”, studies the momentum anomaly. In this essay, I examine the relations of firm characteristics and momentum in US stocks. Momentum effect seems to be less significant in recent years. Most importantly, this paper presents that firm size and growth option may plays an important role in momentum trading strategy. The returns of large and medium winners/losers tend to sustain, while small winners/losers tend to reverse quickly. Also, it also shows that R&D investment enhance the reversal effect of small firms, especially in high-tech industries. The third essay, entitle “Firm Attributes and Momentum Strategies in China”, focus on the emerging market China. This study investigates the momentum and reversal phenomenon in China, based on most up-to-date data. It shows that Chinese stock market experiences barely momentum effect, but the reversal effect is increasingly significant in the long horizon. Additionally, two risk proxies, size and R&D expense, are employed to explain momentum and reversal effect. It shows that the returns of large stocks are more likely to be persistent, while that of small firms are more likely reverse. Moreover, R&D investment reduces reversal effect, especially for small firms.